Reintroducing Flap Reconstruction: One Institution's Safe Return to Flap Surgery during the COVID-19 Pandemic - Chen, Jonlin; Chow, Amanda; Lee, Erica; Wesson, Tristan; Karius, Alexander; Wallam, Sara; Generoso, Matthew; Fadavi, Darya; He, Waverley; Yesantharao, Pooja; Long, Chao; Cooney, Carisa M.; Broderick, Kristen P. (Journal of Reconstructive Microsurgery, 2022)
Background Prevention of nosocomial coronavirus disease 2019 (COVID-19) infection for patients undergoing flap-based reconstructive surgery is crucial to providing care and maintaining operative volume and income to support plastic surgery programs. We conducted this study to (1) determine the postoperative incidence of COVID-19 among patients undergoing flap reconstruction from December 1, 2019 to November 1, 2020 and (2) compare 30-day outcomes between patients who underwent surgery before and during the early pandemic.Methods We conducted an 11-month retrospective cohort study of all patients who underwent flap reconstruction across our institution. We abstracted patient demographics, intraoperative management, COVID-19 testing history, and 30-day postoperative complications from electronic health records. Nosocomial COVID-19 infection was defined as reverse transcription polymerase chain reaction (RT-PCR) viral ribonucleic acid detection within 30 days of patients' postoperative course or during initial surgical admission. We used chi-squared tests to compare postoperative outcomes between patients who underwent surgery before (prior to March 12, 2021, when our institution admitted its first COVID-19 patient) versus during (on/after March 12, 2021) the pandemic.Results Among the 220 patients (mean [standard deviation] age = 53.8 [18.1] years; female = 54.8%) who underwent flap reconstruction, none had nosocomial COVID-19 infection. Five (2%) patients eventually tested COVID-19 positive (median time from surgery to diagnosis: 9 months, range: 1.5–11 months) with one developing partial flap loss while infected. Between patients who underwent free flap surgery before and during the pandemic, there were no significant differences in 30-day takebacks (15.6% vs. 16.6%, respectively; p > 0.999), readmissions (9.4% vs. 12.6%, respectively; p = 0.53), and surgical complications (e.g., total flap loss 1.6% vs. 2.1%, p = 0.81).Conclusion Robust precautions can ensure the safety of patients undergoing flap surgeries across an academic medical institution, even during periods of high COVID-19 admission rates. Further studies are needed to generate evidence-based guidelines that optimize infection control and flap survival for patients undergoing reconstruction.
Keywords: COVID-19; clinical practice guidelines; pandemic; reconstructive surgery; flap reconstruction